Mrs. Roberto : or, The widowy worries of the Moosepath League - Reid, Van (Moosepath League, 2016)
Landing unexpectedly on the farm of the eccentric Fern family, Tobias Walton finds his courtship with Phileda McCannon interrupted, while guileless Joseph Thump enlists the aid of the Moosepath League to rescue a damsel in distress.